Effect of far-infrared therapy device on arteriovenous fistula maturation and lifespan in hemodialysis patients: a randomized controlled clinical trial - Huang, Jianqiang; Zheng, Peilan; Chen, Xiaobin; Zheng, Fan; He, Beibei (Frontiers in Surgery, 2023)
Background: In this study, the effect of far infrared therapy (FIR) on the maturity and longevity of arteriovenous fistula in hemodialysis patients was discussed, and the protective mechanism of AVF induced by FIR therapy was explored, aiming at exploring a new treatment method. Methods: The hemodialysis patients admitted to the Qinghai Provincial People’s Hospital from January 2021 to April 2023 were randomly divided into control group and intervention group, with 40 cases in each group. Among them, the control group was coated with mucopolysaccharide polysulfonate cream; Intervention group: The patients were treated with mucopolysaccharide polysulfonate cream and far infrared radiation at the same time. After 3 months' intervention, the arteriovenous fistula (vein diameter, mature time of arteriovenous fistula, blood flow controlled by pump during dialysis, blood flow of brachial artery during dialysis and the occurrence of complications of internal fistula (oozing, occlusion and infection) and the pain score (numerical rating scale, NRS) of the two groups were compared, and the curative effects were compared. Results: There was no significant difference in general data between the two groups (P>0.05), which indicated that the study was comparable. After 3 months' intervention, the vein diameter, pump-controlled blood flow and brachial artery blood flow in the intervention group were significantly higher than those in the control group (P<0.05). And the maturity time, NRS score and complication rate of arteriovenous fistula were significantly lower than those of the control group (P<0.05). The primary patency rate of AVF in the intervention group was higher than that in the control group, and the overall patency rate between the two groups was statistically significant (P<0.05). Conclusions: As a promising new treatment method, far infrared therapy can effectively promote the maturity of AVF, increase venous diameter, pump controlled blood flow during dialysis, brachial artery blood flow during dialysis, and prolong the service life of AVF.